Measuring Volatility Spillovers among cryptocurrencies: A Generalized VAR approach - MELKI, ABIR (Bankers, Markets & Investors, 2020)
This paper investigates volatility spillovers among six competitor Cryptocurrencies from August 8, 2015 to September 01, 2019. A Generalized VAR framework is used to measure time varying spillovers index. Results provide evidence of (i) a rise in volatility spillovers transmitted among monitored Cryptocurrencies since the second quarter of 2017. (ii) Ethereum acts as the major contributor on spillovers index, contrary to Ripple that presents the main recipient of spillovers. (iii) the pairwise (Monero-Ripple) and (Bitcoin-Ethereum) present a low connectedness level driving consequently beneficial diversification opportunities for cryptocurrency investors.